Membership, belonging, and identity in the twenty-first century. (30th March 2016) - Motteram, Gary
Abstract: This article takes a case study approach to exploring membership, belonging, and identity amongst English language teachers in the twenty-first century. It explores findings from two membership surveys conducted for the International Association of Teachers of English as a Foreign Language (IATEFL), and considers the impact of recommendations emerging from the first survey which were implemented to enable members to engage more fully in the organization. The article shows that a combination of reaching out to the broader community of teachers (using increasingly widespread digital technologies), combined with supporting targeted local actions, not only better enables teacher associations to achieve their mission to serve all their members, but also takes into account the changing nature of belonging and identity of ELT teachers, enabling them to become more engaged and have a stronger voice in the ELT community as a whole.